Pandemics of Late Antiquity - Kozlenko, Alexei V (Journal of the Belarusian State University. Ecology, 2022)
The article deals with the problem of the environmental factors impact on large-scale historical processes. As a rule, historians use political, social and economic factors while explaining such phenomena as the crisis and decline of the Roman empire. This choice is largely determined by the nature of the available sources and the tradition of their interpretation. With the development of archeology in the mid-second half of the XX century, the volume of sources available to researchers has increased significantly. They included not only objects of material culture, but also human remains, plant pollen and ice cores. These data allow us to obtain reliable information about the ecology of a particular region in a particular era. The interpretation of these data indicates that between the second half of the 2 century and the middle of the 6 century, the climate in the ancient Mediterranean experienced a number of unfavorable changes. The average temperature of the entire region has become several degrees lower, the amount of precipitation and harvests has changed. Famine forced the masses of people to abandon their lands and go to the cities in search of food. These disasters coincided with several devastating waves of epidemics that swept around the world. The most devastating of them was the so-called “Justinian plague”, which killed at least 100 million people. The regions with a high level of urbanization and a large trade and craft population suffered the most from the disease. There was a depopulation of entire regions, a significant degradation of the economy and society. The epidemic lasted for almost 200 years and when the disease weakened, the restoration of society took place on a completely different basis compared to the previous era. The changes that took place were large-scale and caused the transition from Antiquity to the Middle Ages. The current situation, when the coronavirus pandemic again threatens the stability of the modern world order, gives additional relevance to the chosen topic.
Keywords: ecology; climate; epidemic; pandemic; plague; Roman Empire; Late Antiquity